“Italy, for Example, Is Just Incredibly Stupid Now”. European Crisis Narrations in Relation to Italy's Response to COVID-19 - Viola, Lorella (Frontiers in Communication, 2022)
Crisis narratives shape public understanding and, consequently, the response to the crisis itself. In the context of the COVID-19 pandemic, when in February 2020 Italy was experiencing more cases than any other country, the Italian response to the crisis originated debates over how to best respond to the outbreak. Informed by Critical Discourse Analysis theory and using narrative networks as a framework for the critical analysis of narratives, this study analyzes the discourse strategies employed by experts, politicians and other social actors from Spain, France, the Netherlands, and the UK when presenting their domestic measures in relation to Italy's response to coronavirus. The analysis shows that the narratives attached to nation-specific decisions were highly culturalized and connected to country-specific shared experiences, such as a sense of national exceptionalism built in opposition with the denigration of Italy as the Other-identity. Attribution of blame and blameworthiness was also found to be a common pattern across countries according to which Italians were framed as wrongdoers but also as deserving blame. The article also presents a comprehensive “timeline of narratives” which opens avenues for a critical reflection on the impact such narratives may have had on the understanding of the crisis, including the creation of a negative climate of division and inappropriate crisis responses.